Understanding turbulence suppression in JET D–T plasma with highly energetic fast ions via global gyrokinetic GENE simulations - A. Di Siena; J. Garcia; G. Merlo; A. Bañón Navarro; F. Sheffield; E. Poli; A. Ishizawa; Ye.O. Kazakov; J. Varela; T. Görler; F. Jenko; JET Contributors; et al. (Nuclear Fusion)
This study focuses on understanding how turbulence is suppressed in particularly heated JET plasma discharges showing enhanced confinement, namely $99896$ , which uses a nearly 50–50 deuterium–tritium mixture, showing signs of enhanced plasma confinement. The discharge was heated primarily using ion-cyclotron-resonance heating, with a small contribution from neutral beam injection, to minimize external torque and toroidal rotation, resembling conditions expected in future fusion reactors. Global gyrokinetic simulations using the GENE code are performed to analyze the turbulent transport and its stabilization mechanisms associated with the improved confinement observed in the experiment. The results reveal that multiple mechanisms contribute to turbulence suppression acting at different radial domains: wave-particle resonance stabilization reduces the fluxes up by 80%, electromagnetic beta-stabilization accounts for a 20%–30% reduction, and toroidal Alfvén eigenmode (TAE) suppression decreases the fluxes up by 80%. This suppression is attributed to an enhancement of zonal flow activity driven by TAEs, whose nonlinear saturation is influenced by the effect of zonal currents. In the presence of an unstable TAE, we observe a shift in the dominant turbulence regime, transitioning from drift-wave turbulence to TAE-dominated turbulence. This transition modifies the cross-phase between the electrostatic potential and temperature fluctuations at TAE scales. However, these changes do not impact turbulence fluxes at ITG scales. These findings highlight the complex interplay between energetic particles, electromagnetic effects, and TAE modes in controlling plasma turbulence and improving confinement in future fusion reactors.